Odpowiedź :
6,1 - ( -2 ¹/₉) =(6 i 1/10) + (2 i 1/9)=(6 i 9/90) + (2 i 10/90)=(8 i 19/90)=8,2(1)
(-⁵/₃ + 3 - 0,5) * (- 1⅕) + ⅕ =[(-5/3)+3-(5/10)]*[(-1 i 1/5)]+(1/5)=[(-50/30)+(90/30)-(15/30)]*[(-6/5)]+(1/5)=[(-50/30)+(90/30)-(15/30)]*[(-6/5)]+(1/5)=(25/30)*(-6/5)+(1/5)=(5/5)*(-1/1)+(1/5)=-1+(1/5)=(-5/5)+(1/5)=(-4/5)
(-⁵/₃ + 3 - 0,5) * (- 1⅕) + ⅕ =[(-5/3)+3-(5/10)]*[(-1 i 1/5)]+(1/5)=[(-50/30)+(90/30)-(15/30)]*[(-6/5)]+(1/5)=[(-50/30)+(90/30)-(15/30)]*[(-6/5)]+(1/5)=(25/30)*(-6/5)+(1/5)=(5/5)*(-1/1)+(1/5)=-1+(1/5)=(-5/5)+(1/5)=(-4/5)
6,1 - ( -2 ¹/₉) =
=61/10+19/9=549/90+190/90=739/90=8i 19/90
(-⁵/₃ + 3 - 0,5) × (- 1⅕) + ⅕ =
=(-5/3 + 5/2) × (- 6/5)+ 1/5=
=(-10/6+15/6)(-6/5)+1/5=
=5/6 ×(-6/5)+1/5=
=-1+1/5=-4/5
=61/10+19/9=549/90+190/90=739/90=8i 19/90
(-⁵/₃ + 3 - 0,5) × (- 1⅕) + ⅕ =
=(-5/3 + 5/2) × (- 6/5)+ 1/5=
=(-10/6+15/6)(-6/5)+1/5=
=5/6 ×(-6/5)+1/5=
=-1+1/5=-4/5